Knowledge, attitude and practice regarding emergency contraceptives among married women of urban slum area - Raikar, Vivek R.; Potdar, Pallavi A.; Potdar, Ashutosh B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unprotected sexual intercourse & contraceptive failure lead to unintended pregnancies & unsafe abortions. Emergency contraceptives offer safe & effective emergency care intervention. The objective was to assess the knowledge, attitude & practice regarding emergency contraceptives among married women of reproductive age group and to study the influence of educational status on the awareness & willingness to use emergency contraceptives. Methods: Community based cross-sectional study was conducted from 1st May 2011- 30th Jan 2012 in 286 married women in age group 15-45 yrs residing in the field practice area of Urban Health Centre attached to Department of Community Medicine, Bagalkot, Karnataka. Data was collected by personal interview method with house-to-house visit by administering structured, pre-tested questionnaire to elicit information on knowledge, attitude & practice regarding emergency contraceptives. Chi square test was used to estimate statistical significant differences. Results: Out of total 286 females, majority were in the age group of 20-30 yrs, 94.40% were Hindus, majority i.e. 81.74% were homemakers & 59.79% were illiterate, 72.48% belonged to lower social class (class IV & V) according to modified B.G. Prasad classification. We found that 56% women had accepted one or other contraceptives. Only 12% women were aware about EC while among literates, 29% were aware about EC out of which only 4.38% had idea about the correct dosage, availability and side effects of the pills. Willingness to use EC was seen among 29% of women out of which majority i.e. 54.78% were literate and 68.32% were employed. Among the study population 3% of the women actually practiced emergency contraceptives. Educational status of females had significant association with awareness about EC pill (χ2=29.46) and positive attitude towards usage of EC pill (χ2=27.32). Conclusion: The awareness as well as the usage of emergency contraceptives is very low in our society. Still we are facing the problem of illiteracy in our country which is predominant in slum areas. More emphasis should be given to female education and empowerment in order to make them capable of taking decisions regarding their own reproductive health.